BATCH SCHEDULING MODEL ON FLEXIBLE FLOW LINE WITH MISSING OPERATIONS TO MINIMIZE TOTAL ACTUAL FLOW TIME - RAHMAWATI, SINTA
This study discusses a batch scheduling model with criteria the total minimization of actual flow time on flexible flow line with missing operations. Missing operations is a condition when not all jobs are processed at each stage. In this study, the stages in flexible flow line are divided into three types, namely: stages that do not have successors, stages that have successors and predecessors, and stages that have no predecessor. The decision variables in this study are the number and size of batches and the batch sequence that will be processed. Heuristic algorithms are proposed to solve problems in the batch scheduling model with the criteria the total minimization of actual flow time on flexible flow line with missing operations. The solution of the proposed algorithm starts with determining the batch number and the batch size, and then determines the batch sequence produced. Determination of batch number and batch size is carried out at stages that do not have successors by using algorithm 5.1 on Halim et al (1994), namely the problem of multi item batch scheduling on a single machine. The scheduling process considers the existence of a batch distribution to be processed simultaneously into several available machines. The test results show that the proposal model is sensitive to the number of demand’s changes, processing time, setup time and the number of machine. On the contrary, the solution on the proposed algorithm is not sensitive to the due date parameter’s changes.